(untitled) (Fiep Bulletin - online, 2015)
Objective of the study is to diagnosis the genetic profiles of the Brazilian election of canoeing slalom through the dermatoglyphia. Analyzed through the descriptive statistics and following dermatoglyphics analysis of Cummins & Midlo (1942). Population was composed for the athletes of the Brazilian election of permanent, masculine canoeing slalom, being N=15, C1(N=3), C2(N=4) and K1(N=8). Resulted: the C1 was established to digital formula AL=66,7%, L>W=33,3%, SQTL=116 and D10=11,7; the group C2 L>W=50%, AL=25%, 10L=25%, SQTL=131,5 and D10=10,2 and group K1 L>W=37,5%, L=W=37,5%, ALW=12,5%, 10L=12,5%, SQTL=153,9 and D10=13,4. For the results we observe that: the C1 presents characteristics of speed with resistance, predominating the speed, explosive force confirmed by the SQTL=116 and D10=11,7. The C2 presents speed with resistance, explosive force and moderate coordinative index (SQTL/D10), confirmed for D10=10,2 and SQTL=131,5 and the K1 presents speed with resistance, predominating the speed and complex propriocepção confirmed by the SQTL=153,9, D10=13,4 and L>W=37,5%.